Integrated water resource management to address the growing demand for food and water in South Asia - Birendra, K. C.; McIndoe, I.; Schultz, B.; Prasad, K.; Bright, J.; Dark, A.; Pandey, Vishnu Prasad; Chaudhary, A.; Thapa, P. M.; Perera, R.; Dangi, D. R. (Wiley, 2021)
With the increasing population and accelerated urbanization, demands for water are rising for different sectors around the world, including in South Asia. Integrated water resource management (IWRM) offers a promising potential to address multifaceted water demands. This study therefore aimed to address this issue by (i) reviewing key issues related to water, land, and food in South Asian countries, (ii) exploring the prevalent irrigation management strategies in those countries, and (iii) examining the IWRM situation based on a Nepalese case study, and it proposes some options to support effective implementation of IWRM.